Legal Synchronization of Bankruptcy Asset Distribution: Prioritizing Workers Over State Taxes (An Analysis of the Constitutional Court Decision No. 67/PUU-XI/2013 Regarding the Position of Workers and State Taxes in Bankruptcy Asset Distribution) - Andre Rizaldy; Muthia Sakti; Iwan Erar Joesoef (International Forum of Researchers and Lecturers, 2025)
This study examines the legal conflict between workers' wage claims and state tax obligations in bankruptcy proceedings under Indonesian law, focusing on the constitutional imperative to prioritize workers' rights. The Introduction contextualizes the tension between Article 95(4) of the Labor Law, which mandates wage prioritization, and tax legislation granting precedence to state claims, highlighting the landmark Constitutional Court Decision No. 67/PUU-XI/2013 that affirmed workers' constitutional rights to timely wages. Employing a Method of normative legal research, the analysis integrates statutory and case approaches, reviewing laws on bankruptcy (UU No. 37/2004), labor rights, and taxation, alongside judicial decisions and international frameworks like ILO Conventions No. 100 and 111. Results reveal that while the Constitutional Court’s decision established workers’ absolute priority over tax claims, regulatory disharmony persists due to conflicting provisions in the Tax Law (UU KUP) and the 2020 Job Creation Law (UU Cipta Kerja), which ambiguously subordinates tax claims only to secured creditors. Discussion underscores the necessity for legal synchronization to align labor and tax regulations, ensuring compliance with Gustav Radbruch’s principles of legal certainty and Hans Kelsen’s normative hierarchy. The study advocates legislative reforms to codify workers’ priority in bankruptcy, drawing parallels with Malaysia’s Employment Act 1955 and France’s AGS system, which institutionalize wage protection. By addressing regulatory contradictions, Indonesia can harmonize constitutional mandates with fiscal policies, balancing social justice and economic stability.